A phase II evaluation of elesclomol sodium and weekly paclitaxel in the treatment of recurrent or persistent platinum-resistant ovarian, fallopian tube or primary peritoneal cancer: An NRG oncology/gynecologic oncology group study - Monk, Bradley J.; Kauderer, James T.; Moxley, Katherine M.; Bonebrake, Albert J.; Dewdney, Summer B.; Secord, Angeles Alvarez; Ueland, Frederick R.; Johnston, Carolyn M.; Aghajanian, Carol (Gynecologic oncology, 2018)
Preclinical data suggest elesclomol increases oxidative stress and enhances sensitivity to cytotoxic agents. The objective of this prospective multicenter phase 2 trial was to estimate the activity of IV elesclomol plus weekly paclitaxel in patients with platinum-resistant recurrent ovarian, tubal or peritoneal cancer through the frequency of objective tumor responses (ORR). Patients with measurable disease, acceptable organ function, performance status ≤ 2, and one prior platinum containing regimen were eligible. A two-stage design was utilized with a target sample size of 22 and 30 subjects, respectively. Prior Gynecologic Oncology Group studies within the same population involving single agent taxanes showed an ORR of approximately (20%) and served as a historical control for direct comparison. The present study was designed to determine if the regimen had an ORR of ≥40% with 90% power. Fifty-eight patients were enrolled, of whom 2 received no study treatment and were inevaluable. The median number of cycles was 3 (268 total cycles, range 1–18). The number of patients responding was 11 (19.6%; 90% CI 11.4% to 30.4%) with one complete response. The median progression-free survival and overall survival was 3.6 months and 13.3 months, respectively. The median ORR duration was 9.2 months. Percentages of subjects with grade 3 toxicity included: Neutropenia 9%; anemia 5%; metabolic 5%; nausea 4%; infection 4%; neurologic (mostly neuropathy) 4%; and vascular (mostly thromboembolism) 4%. There were no grade 4 toxicities reported. This combination was well tolerated but is unworthy of further investigation based on the proportion responding [ClinicalTrials.gov Identifier: NCT00888615]. •Elesclomol increases reactive oxygen species and enhances the efficacy of chemotherapy in preclinical models.•There is no added clinical benefit to paclitaxel when elesclomol is added to treatment of recurrent ovarian cancer.•The combination of paclitaxel and elesclomol is well tolerated.